Output only based modal analysis of a reduced scale building using digital camera images - Sabino, Danilo Damasceno [UNESP]; Pereira, João Antonio [UNESP]; Abreu, Gustavo Luiz C. M. [UNESP]; Cunha, A.; Caetano, E.; Ribeiro, P.; Muller, G. (European Assoc Structural Dynamics, 2014)
The article discusses a proposal of displacement measurement using a unique digital camera aiming at to exploit its feasibility for Modal Analysis applications. The proposal discusses a non-contact measuring approach able to measure multiple points simultaneously by using a unique digital camera. A modal analysis of a reduced scale lab building structure based only at the responses of the structure measured with the camera is presented. It focuses at the feasibility of using a simple ordinary camera for performing the output only modal analysis of structures and its advantage. The modal parameters of the structure are estimated from the camera data and also by using ordinary experimental modal analysis based on the Frequency Response Function (FRF) obtained by using the usual sensors like accelerometer and force cell. The comparison of the both analysis showed that the technique is promising noncontact measuring tool relatively simple and effective to be used in structural modal analysis
Keywords: Image processing; Output only modal analysis; Non-contact